2020
DOI: 10.1136/bmjopen-2019-035501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between urban and rural mortality in patients with acute myocardial infarction: a nationwide longitudinal cohort study in South Korea

Abstract: ObjectivesThis study investigated the risk associated with interhospital transfer of patients with acute myocardial infarction (AMI) and clinical outcomes according to the location of the patient’ residence.DesignA nationwide longitudinal cohort.SettingNational Health Insurance Service database of South Korea.ParticipantsThis study included 69 899 patients with AMI who visited an emergency centre from 2013 to 2015, as per the Korea National Health Insurance Service database.Primary outcome measureThe clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Studies based on US contexts have shown that patients with acute myocardial infarction (AMI) have higher mortality rates in rural hospitals than in urban hospitals [ 1 , 2 , 3 ]. Similar results were also found in South Korea [ 4 ]. While urban–rural differences in treatment and outcomes for patients with AMI are well studied in the United States, much larger gaps in knowledge exist in other countries, especially in low- and middle-income countries (LMIC).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies based on US contexts have shown that patients with acute myocardial infarction (AMI) have higher mortality rates in rural hospitals than in urban hospitals [ 1 , 2 , 3 ]. Similar results were also found in South Korea [ 4 ]. While urban–rural differences in treatment and outcomes for patients with AMI are well studied in the United States, much larger gaps in knowledge exist in other countries, especially in low- and middle-income countries (LMIC).…”
Section: Introductionsupporting
confidence: 89%
“…Healthcare disparities between urban and rural areas have attracted increasing attention around the world [ 1 , 2 , 3 , 4 , 5 ]. Studies based on US contexts have shown that patients with acute myocardial infarction (AMI) have higher mortality rates in rural hospitals than in urban hospitals [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ACS patients from the rural areas had a three-to-four -fold increased risk of in-hospital mortality compared to those from the urban areas. Studies on ACS from developed countries also show considerable disparity when mortality is stratified by urbanization [ 28 30 ] The higher mortality rate among ACS patients from a rural area in the current study is partially explained by prolonged pre-hospital delay in rural residents and difference in socioeconomic status which could lead to a difference in treatment and related factors. Since more rural patients die before reaching hospitals, the actual death rate is likely to be greater than reported here.…”
Section: Discussionmentioning
confidence: 74%
“…The primary exposure of this study was IHT, which was defined as a transfer to another emergency room. The IHT should be within one day of visiting an emergency room between acute care facilities to ensure that the visit was not from a long-term facility to an acute care facility [ 15 ]. The outcome of interest was the all-cause mortality assessed at 30 days and one year after the onset of AMI.…”
Section: Methodsmentioning
confidence: 99%